PEMIKIRAN EKONOMI POLITIK INTERNASIONAL HIZBUT TAHRIR - Zaki, Irham (Jurnal Review Politik, 2013)
This study describes the thinking of Hizbut Tahrir about some of the themes of political economy. It should be studied, because they spreads the ideas of Islamic economics which aimed to political objectives; namely establishing the Caliphate in the world. With the approach of the literature, the results showed that the economic issues which were highlighted by Hizbut Tahrir revolves around the ideas related to the economy from the West, which have political motive. This can be assessed from debt relief, privatization, globalization, and free markets. Hizbut Tahrir considered that the condition of Muslims today are weak both economic and political aspects. On the other hand, Western countries propagate their ideas strongly to Muslim countries.